#1**+10 **

Multiply both sides by sinx

3tanx*sinx = 8

tanx = sinx/cosx so the above can be written as

3*sin^{2}x/cosx = 8

Multiply both sides by cos x

3*sin^{2}x = 8cosx

sin^{2}x = 1 - cos^{2}x so the above becomes

3*(1 - cos^{2}x) = 8cosx

3 - 3cos^{2}x = 8cosx

Add 3cos^{2}x to both sides of the equation

3 = 3cos^{2}x + 8cosx

Subtract 3 from both sides of the equation

0 = 3cos^{2}x + 8cosx - 3

.

Alan
Apr 12, 2015

#1**+10 **

Best Answer

Multiply both sides by sinx

3tanx*sinx = 8

tanx = sinx/cosx so the above can be written as

3*sin^{2}x/cosx = 8

Multiply both sides by cos x

3*sin^{2}x = 8cosx

sin^{2}x = 1 - cos^{2}x so the above becomes

3*(1 - cos^{2}x) = 8cosx

3 - 3cos^{2}x = 8cosx

Add 3cos^{2}x to both sides of the equation

3 = 3cos^{2}x + 8cosx

Subtract 3 from both sides of the equation

0 = 3cos^{2}x + 8cosx - 3

.

Alan
Apr 12, 2015